(3cQI GdSdI ddLejYs - (3eYhV MSf SjOs ((3GdbGgQIs (3OGQ GdacQ GdYQHjs, 2003)
(3JfGhd JGQjN cQI GdSdI eJWQbG Edi Cge YfGUQ GddYHI (B:(3GdEYOGO GdaQOj GdegGQj GdgLhej h GdOaGYj ,cPdc YQV HYV GdWQb GdOaGYj ,h TQM WQb GdgLhe hGge GdNWW GdeYJeOI aj QjGVI cQI GdSdI(B.s